2020
DOI: 10.1111/dth.14236
|View full text |Cite
|
Sign up to set email alerts
|

Collision tumors: A review of their types, pathogenesis, and diagnostic challenges

Abstract: A collision tumor is a neoplastic lesion comprised of two or more distinct cell populations that maintain distinct borders. Collision tumors, which are rare but well documented, can be composed of two benign tumors, a benign and malignant tumor, and two malignant tumors. Although case reports and reviews on specific types of collision tumors exist, a cohesive source discussing these tumors is lacking. We critically reviewed the literature by analyzing case reports and retrospective studies in order to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 21 publications
(47 reference statements)
0
44
0
6
Order By: Relevance
“…Collision tumors are two or more neoplasms of distinct cell populations occurring at the same cutaneous site [ 5 ]. The mechanism for the development of collision tumors is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collision tumors are two or more neoplasms of distinct cell populations occurring at the same cutaneous site [ 5 ]. The mechanism for the development of collision tumors is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This theory hypothesizes that collision tumors result from two different clones of neoplastic cells by chance alone. Other theories include field cancerization, stem cell cancerization, and epithelial or stromal changes induced by the first neoplasm stimulates development of the second neoplasm [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term collision tumor refers to the presence of coexistent but independent tumors that are histologically distinct [5]. Collision tumors are believed to result from two separate but adjacent neoplasms (biclonal malignant transformation) and are different from composite tumors, which are thought to arise from a multidirectional differentiation of a single neoplasm [6]. Collision tumors imply the coexistence of two discrete histogenetically and genetically distinct cell types arising from a common source.A recent study reported the immunohistochemical (IHC) and the fluorescence in situ hybridization (FISH) characteristics of 17 tumors of the kidney with a papillary component admixed with another histotype [7].…”
Section: Introductionmentioning
confidence: 99%
“…Un tumor de colisión es aquel conformado por dos poblaciones celulares diferentes, microscópicamente adyacentes una a la otra, pero que mantienen bordes diferenciados. Estas asociaciones incluyen tumores benignos, malignos o una combinación de ellos 1,2 .…”
Section: Introductionunclassified
“…El mecanismo etiopatogénico que genera los tumores de colisión no está totalmente dilucidado; sin embargo, la teoría más aceptada postula que las dos neoplasias surgirían de clones celulares diferentes y su asociación sería solo una coincidencia 3 . Otra teoría sostiene que, en un área de piel fotodañada, aumenta el riesgo de aparición de distintos tumores adyacentes entre sí; por último, se propone la teoría de la interacción, según la cual, a través de un efecto paracrino, un tumor puede producir cambios estromales que inducirían a la formación de la segunda neoplasia 1,4 .…”
Section: Introductionunclassified